PRAKTIK PERATAAN LABA UNTUK MEMPERTAHANKAN KINERJA KEUANGAN PERUSAHAAN DI INDONESIA - Rosalina, Kiki Sany (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The research aims to identify if income smoothing practices administered by the companies are motivated to maintain their financial performance. The population of this study is 43 banking companies listed in the Indonesian Stock Exchange until 2015; 37 of which are purposively selected as the research samples as they fulfill the settled criteria. The data are analyzed by sample test and correlation analysis using SPSS version 20. The method used to determine the income smoothing practices is Eckel Index. The result of the study confirms the presence of income smoothing practices by the banking companies regardless the fact that they are not applied for the sake of maintaining financial performance.Keywords: Income smoothing practice, Eckel index, Financial performance